ANALISIS PENGENDALIAN KUALITAS MENGGUNAKAN METODE SIX SIGMA PADA PROSES INJECTION MOULDING PRODUK COVER TANK DI PT TOKYO SEIMITSU BUHIN - Gracia Maura Hosiana Martua (2023)
PT Tokyo Seimitsu Buhin is a company operating in the injection molding field. This company produces various types of plastic products for electronic applications, one of which is the cover tank product which is part of the printer. From the data obtained for 4 months, it is known that there are several types of defects that exceed the tolerance limit set by the company, which is more than 2%. This study aims to improve product quality by reducing defects through a six sigma approach involving define, measure, analyze, improve, and control stages. The calculation results show an average DPMO of 11,771 with a sigma level of 3.7. The results of the pareto diagram analysis identify that the biggest type of defect is scratch, and the factors that affect defects include humans, methods, materials, machines, and the environment which are obtained through fishbone diagrams. The dominant main causal factor is the human factor, with an RPN value of 344 based on the calculation of the FMEA table. Proposed improvements that can be made include socializing the work instructions used, creating checksheets in the wi-checking process, adding internal operator training, implementing the 5R work culture to all employees and creating supplier evaluation forms. By implementing several improvements to the company, it resulted in an increase in the sigma value of 0.342 and a decrease in the DPMO value of 6912.